Cassini multi‐instrument assessment of Saturn's polar cap boundary. Issue 10 (13th October 2014) - Jinks, S. L.; Bunce, E. J.; Cowley, S. W. H.; Provan, G.; Yeoman, T. K.; Arridge, C. S.; Dougherty, M. K.; Gurnett, D. A.; Krupp, N.; Kurth, W. S.; Mitchell, D. G.; Morooka, M.; et al.
Abstract We present the first systematic investigation of the polar cap boundary in Saturn's high‐latitude magnetosphere through a multi‐instrument assessment of various Cassini in situ data sets gathered between 2006 and 2009. We identify 48 polar cap crossings where the polar cap boundary can be clearly observed in the step in upper cutoff of auroral hiss emissions from the plasma wave data, a sudden increase in electron density, an anisotropy of energetic electrons along the magnetic field, and an increase in incidence of higher‐energy electrons from the low‐energy electron spectrometer measurements as we move equatorward from the pole. We determine the average level of coincidence of the polar cap boundary identified in the various in situ data sets to be 0.34° ± 0.05° colatitude. The average location of the boundary in the southern (northern) hemisphere is found to be at 15.6° (13.3°) colatitude. In both hemispheres we identify a consistent equatorward offset between the poleward edge of the auroral upward directed field‐aligned current region of ~1.5–1.8° colatitude to the corresponding polar cap boundary. We identify atypical observations in the boundary region, including observations of approximately hourly periodicities in the auroral hiss emissions close to the pole. We suggest that the position of the southern polar cap boundary is somewhat ordered by the southern planetary period oscillation phase but that it cannot account for the boundary's full latitudinal variability. We find no clear evidence of any ordering of the northern polar cap boundary location with the northern planetary period magnetic field oscillation phase.